Evaluation of Three Nucleic Acid Amplification Methods for Direct Detection of Mycobacterium tuberculosis Complex in Respiratory Specimens - Wang, S. X. (American Society for Microbiology, 1999)
Two hundred thirty respiratory specimens from 230 patients were analyzed by using COBAS AMPLICOR PCR, Amplified Mycobacterium tuberculosis Direct Test, and ligase chain reaction methods. Results were compared with those of smear microscopy and radiometric culture (Bactec) methods. No significant differences were observed among the results of the three methods, which are acceptable for direct detection of M. tuberculosis complex in respiratory specimens.